2014
DOI: 10.2337/dc14-1683
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activation Patterns Under Different Working Memory Loads in Patients With Type 2 Diabetes

Abstract: OBJECTIVEType 2 diabetes mellitus (T2DM) has important effects on cognition and the risk for Alzheimer disease (AD). Working memory (WM) is a susceptible cognitive domain of mild cognitive impairment and AD. Thus, the identification of brain activation patterns under different WM loads can potentially enhance our understanding of the mechanisms underlying cognitive dysfunction in T2DM. RESEARCH DESIGN AND METHODSThe current study assessed the effects of T2DM on cognitive performance and explored the related ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 40 publications
3
36
1
1
Order By: Relevance
“…These studies have revealed associations among impaired cognition, altered activation, and decreased functional connectivity (8)(9)(10)(11)(12)(13)(14). Although functional connectivity was measured by correlating signal time series of various and a priori-selected cerebral regions, aberrant connections outside these predefined regions remain undiscovered.…”
mentioning
confidence: 99%
“…These studies have revealed associations among impaired cognition, altered activation, and decreased functional connectivity (8)(9)(10)(11)(12)(13)(14). Although functional connectivity was measured by correlating signal time series of various and a priori-selected cerebral regions, aberrant connections outside these predefined regions remain undiscovered.…”
mentioning
confidence: 99%
“…Brain regions showing decline in metabolism from ADT overlap with brain regions with metabolic decline from Alzheimer’s disease (AD) as well as type-2 diabetes. 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…8 Declines in executive function, are often prominent along with memory declines in AD patients as well as in type-2 diabetes. 43,51 …”
Section: Discussionmentioning
confidence: 99%
“…Impaired cognition functions in patients with T2DM were manifested in a variety of domains, such as attention [14,15,16], execution [14,15,16,17,18], information processing speed [9,14,16,18,19,20], working memory [14,15,17,18], and verbal memory [16,20,21,22,23]. Impaired cognition functions were associated with not only subcortical ischemic changes in the brain but also brain atrophy [14].…”
Section: Pathological Mechanisms Underlying the Impaired Cognition Fumentioning
confidence: 99%